Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

1. The figure shows a graph of the function of f(x) in the xy-coordinate plane, with the vertex at (1,9) and the zeros
at -2 and 4.
x
5 6 7 8 9
The function g is defined by g(x) = -3x + 2. Which statements are true? Select ALL that apply.
f{-2) is greater than g(-2).
f{-1) is less than g(-1).
f{0) is greater than g(0)
f(1) is less than g(1).
f(2) is greater than g(2).


1 The Figure Shows A Graph Of The Function Of Fx In The Xycoordinate Plane With The Vertex At 19 And The Zeros At 2 And 4 X 5 6 7 8 9 The Function G Is Defined class=

Sagot :

Answer:

f{0) is greater than g(0) and f(2) is greater than g(2).

Step-by-step explanation:

f{0) is greater than g(0) = f(0)=8  and g(0)=2

f(2) is greater than g(2) = f(2)=8 and g(2)= -4

The two statements that are correct are f(0) is greater than g(0), and f(2) is greater than g(2).

What is the general equation of parabola?

The general equation of a parabola is given as,

[tex]y=a(x-h)^2+k[/tex]

where (h,k) is the coordinate of the vertex of the parabola.

The equation of the parabola with vertex (1,9) can be written as,

[tex]y=a(x-h)^2+k\\\\y=a(x-1)^2+9[/tex]

Now, the value of a can be found by putting one zero of the parabola,

[tex]y=a(4-1)^2+9\\\\0=a(3)^2+9\\\\-9=a(3)^2\\\\-9=a9\\\\a=-1[/tex]

Thus, the equation of the parabola can be written as y=-(x-1)²+9.

A.) The value of the two functions when the value of x is -2 can be written as,

[tex]f(x)=-(x-1)^2+9\\\\f(-2)=-(-2-1)^2+9\\\\f(-2)=0[/tex]

[tex]g(x) = -3x + 2\\\\g(-2) = -3(-2) + 2\\\\g(-2)=8[/tex]

Therefore, f(-2) is less than g(-2).

B.) The value of the two functions when the value of x is -1 can be written as,

[tex]f(x)=-(x-1)^2+9\\\\f(-1)=-(-1-1)^2+9\\\\f(-2)=5[/tex]

[tex]g(x) = -3x + 2\\\\g(-1) = -3(-1) + 2\\\\g(-1)=5[/tex]

Therefore, f(-1) is equal to g(-1).

C.) The value of the two functions when the value of x is 0 can be written as,

[tex]f(x)=-(x-1)^2+9\\\\f(0)=-(0-1)^2+9\\\\f(0)=8[/tex]

[tex]g(x) = -3x + 2\\\\g(0) = -3(0) + 2\\\\g(0)=2[/tex]

Therefore, f(0) is greater than g(0).

D.) The value of the two functions when the value of x is 1 can be written as,

[tex]f(x)=-(x-1)^2+9\\\\f(1)=-(1-1)^2+9\\\\f(1)=9[/tex]

[tex]g(x) = -3x + 2\\\\g(1) = -3(1) + 2\\\\g(1)=1[/tex]

Therefore, f(1) is greater than g(1).

E.) The value of the two functions when the value of x is 2 can be written as,

[tex]f(x)=-(x-1)^2+9\\\\f(2)=-(2-1)^2+9\\\\f(2)=8[/tex]

[tex]g(x) = -3x + 2\\\\g(2) = -3(2) + 2\\\\g(2)=-4[/tex]

Therefore, f(2) is greater than g(2).

Thus, the two statements that are correct are f(0) is greater than g(0), and f(2) is greater than g(2).

Learn more about Equation of Parabola:

https://brainly.com/question/4074088

Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.